Chitosan-Graphene Oxide 3D scaffolds as Promising Tools for Bone Regeneration in Critical-Size Mouse Calvarial Defects. Issue 1 (December 2017) - Hermenean, Anca; Codreanu, Ada; Herman, Hildegard; Balta, Cornel; Rosu, Marcel; Mihali, Ciprian; Ivan, Alexandra; Dinescu, Sorina; Ionita, Mariana; Costache, Marieta
Abstract Limited self-regenerating capacity of human skeleton makes the reconstruction of critical size bone defect a significant challenge for clinical practice. Aimed for regenerating bone tissues, this study was designed to investigate osteogenic differentiation, along with bone repair capacity of 3D chitosan (CHT) scaffolds enriched with graphene oxide (GO) in critical-sized mouse calvarial defect. Histopathological/histomorphometry and scanning electron microscopy(SEM) analysis of the implants revealed larger amount of new bone in the CHT/GO-filled defects compared with CHT alone (p < 0.001). When combined with GO, CHT scaffolds synergistically promoted the increase of alkaline phosphatase activity bothin vitro andin vivo experiments. This enhanced osteogenesis was corroborated with increased expression of bone morphogenetic protein (BMP) and Runx-2 up to week 4 post-implantation, which showed that GO facilitates the differentiation of osteoprogenitor cells. Meanwhile, osteogenesis was promoted by GO at the late stage as well, as indicated by the up-regulation of osteopontin and osteocalcin at week 8 and overexpressed at week 18, for both markers. Our data suggest that CHT/GO biomaterial could represent a promising tool for the reconstruction of large bone defects, without using exogenous living cells or growth factors.